(untitled) (Linguostylistic Studies, 2015)
The article is dedicated to the analysis of idiostyle of Sydir Vorobkevych (1836–1903), a talented Bucovynean writer, whose works embrace poetry, prose and drama and who was a leading figure in establishing and developing the Ukrainian literary language in Bucovyna of the second half of the 1800s. The language of S. Vorobkevych’s works passes the local features of speech of Bukovina, representing the elements of south-west dialect, and also includes quite a bit borrowing from the European languages, that was typical for the variant of literary language of Western Ukraine of the second half of ХІХ century. Dialectal vocabulary along with literary ‒ one of language dominants of individually-authorial manner of letter, by means of that the nationally-ethnographic and regional colours is reproduced. Key words: idiostyle, language dominant, dialecticisms. References